Preliminary study of ice flow observations along traverse routes from coast to Dome Fuji, East Antarctica by differential GPS method - Hideaki Motoyama; Hiroyuki Enomoto; Teruo Furukawa; Kokichi Kamiyama; Hitoshi Shoji; Takayuki Shiraiwa; Kazuo Watanabe; Kunihisa Namasu; Hisataka Ikeda (Nankyoku shiryo, 1995)
Ice flow has been observed along traverse routes from S16 to Dome Fuji, East Antarctica using the differential GPS (Global Positioning System) method since 1992. This positioning method is easier to use in the field than the satellite doppler positioning system (JMR) or triangle chain method. The vertical and horizontal error of positioning was within 1ppm of base line. The horizontal speed and direction of ice flow were almost the same both years at each site.